Measuring patient preferences through the time trade-off method for orthopedic conditions on large samples - Yen, Talitha; Rodrigues, Clarissa Garcia; Oliveira, Aline Chotte de; Calvo, Paulo Rafeal Sanches; Mather, Richard; Routh, Jonathan; Vissoci, João Ricardo Nickenig (Gestão e Sociedade, 2017)
Background: In cost-effectiveness analyses, Quality-Adjusted Life Years (QALY) remains one of the most widely used health effect measure. Among the various methods of estimating utility values, time trade-off (TTO) has traditionally been one of the dominant methods for eliciting utilities, however it has been presenting several practical impediments to provide a high and fast collecting process. Objective: To test a method of collecting TTO-derived utilities using a platform called Amazon’s Mechanical Turk (MTurk) that provides reliable, fast and inexpensive data. Methods: A pre-programmed interactive questionnaire was design to simulate a live TTO interview using Qualtrics. To validate the results members of the Research on Research (RoR) Group not aware of the research agreed to answer the same questions on a videoconference live interview. We determined feasibility through assessment quality and cost/benefit relation indicators. In addition, this paper followed the framework for reproducible research reports proposed by our group. Results: Results: Our results showed that the MTurk population is representative of the US population (based on 2012 census) and there were no differences on the willingness to live when comparing the MTurk sample and the live interview sample, and also no differences of the WTL when comparing the different questionnaire designs developed. Preference results showed differences only for race (between others and African-Americans, and other and white), and overall median values of 0.83 (Q1=0.83;Q3=0.90). Conclusions: MTurk is a reliable web place to collect large sample using the TTO method, and should be used to collect utility data for CEA.